Ductular reaction or hepatic reparative complex: immunohistochemical features in liver cirrhosis in patients with chronic hepatitis - V. A. Tumanskiy; S. V. Fen' (Zaporozhye State Medical University, 2018)
Until recently, a discussion about the mechanisms of development and the biological role of the ductular reaction, which develops in patients with chronic liver diseases continues among hepatologists and pathomorphologists. Purpose of the study. To characterize the pathomorphological features and significance of the ductular response in liver cirrhosis in patients with chronic non-alcoholic, alcoholic and viral hepatitis in hepatobioptats with the use of immunohistochemical (IHC) techniques. Material and methods of investigation. Histological, histochemical and IHC study of the ductular liver reaction in liver biopsies of 52 patients aged 24 to 66 years with cirrhosis of the liver on the background of non-alcoholic steatohepatitis (13 patients), and alcoholic steatohepatitis (13 patients) and on the background of chronic viral hepatitis C (10 patients, 26-47 years), as well as those suffering from severe biliostasis (8 patients) and focal nodular liver hyperplasia (8 patients). Results. The ductular reaction can be detected in the active phase with maximum manifestations in patients with liver cirrhosis on the background of chronic hepatitis, it may have an average or weak degree of severity; in a significant number of patients, the effects of the ductular reaction of the liver are revealed. Cellular chains and groups of cells with the immunophenotype of the progenitor cells of the liver appear in the active phase of the ductular reaction at the periphery of the hepatic lobules in the projection of the Goering canals, in the fibrotically altered portal tracts, in the subcapsular zone of the liver and in the thickened fibrosis septa (c-kit CD117+, CD34+, CD56+ CK7-, CK19-, Hepar-) without presence of figures of mitosis or increased level of expression of Кі-67 in them. In small ductules localized in the projection of the Goering canals, single cells with the expression of c-kit CD 117+, CD44 Std./HCAM+, CD34+, CD56+, expressing the markers of biliary (CK7+, CK19+) and hepatocyte (Hepar+, α-fetoprotein+) differentiation are revealed. Cellular chains and ductules in the intermediate zones of the hepatic lobules are represented by cells of biphasic differentiation: biliary (CK7+, CK19+), hepatocyte (Hepar+) differentiation and intermediate hepatobiliary CK7+ cells. Hepatocyte differentiation of progenitor cells in lobules of the liver is facilitated by local expression of laminin by perisinusoidal stellate cells. New pseudolobes arise in the active phase of the ductular reaction in the lobes with perisinusoidal pericellular fibrosis from disorderly located large hepatocytes without linear perisinusoid spaces and centrolobular veins, with the presence of "intermediate" SC7+ hepatocytes on the periphery. One-two-row chains and ductules from SC7+ and CK19+ cells dominate in the fibro-altered portal tracts, septa and the subcapsular zone of the liver among the collagen fibers of I, III, IV type and the processes of α-SMA+ myofibroblasts, and small short chains from Hepar+ and α- fetoprotein-cells. When the severity of micronodular liver cirrhosis increases, when the area of hepatic lobules and pseudotypes becomes equal to or less than the area of the surrounding fibrosis, there is a parallel increase in the number of Ki-67+ cells in portal-lobular ductules and chains, as well as the number of Ki-67+ hepatocytes in hepatic lobules and pseudolobes. The long-term consequences of the ductular reaction in liver cirrhosis reflect the presence of the different number of bile-free ductules with CK7 + epithelium in the fibrous tissue of portal tracts, septa and under the liver capsule. In the lobules of the liver with perisinusoidal pericellular fibrosis, fuzzy outlines of hepatocyte hyperplasia without ordered sinusoids and liver-celled beams are found. Conclusions. The ductular reaction in liver cirrhosis in patients with chronic non-alcohol, alcoholic and viral hepatitis is the process of activation and evolution of a complex liver repair complex aimed at replenishing the deficit of hepatocytes and biliary structures. The reparative process, activating by liver cirrhosis on the background of the disturbed portal-lobular intercellular matrix and the progressive deficit of hepatocytes, does not provide the reconstruction of full-fledged liver structures, it is discordant towards the creation of new, functionally low-value hepatocellular pseudolobes and the accumulation of biliary terminals in fields of portal-septal fibrosis.